Dynamics of Serum Cytokines During Resection Surgery for Malignant Neoplasms in the Lungs - A. O. Soloviev; V. T. Dolgikh; O. N. Novichkova; N. V. Govorova; O. V. Leonov; O. V. Sokolova (Общая реаниматология)
Purpose — to carry out a comparative assessment of inflammation based on evaluation of intraoperative and early postoperative dynamics of blood serum cytokines in pulmonary malignant neoplasm patients in different anesthesia and analgesia settings.Material and methods. 24 patients of 45 to 50 years of age divided into 2 groups were examined. All patients suffered from verified new onset malignant neoplasms without true signs of metastases. Tumor differentiation by morphology was not undertaken since that was beyond the study design. Patients did not receive radio- or chemotherapy. In Group I (the main group, n=12), a multimodal combined anesthesia [1] followed by extended postoperative epidural analgesia was applied. In Group II (the comparison group, n=12), a combined general anesthesia including mechanical lung ventilation followed by morphine analgesia was used. 4 study points were determined: prior to induction, and one, 12, and 24 hours post-surgery.Results. 12 hours after surgery completion, the concentration of TNFα in the main group was lesser by 57.1% vs. the comparison group; by the end of the first 24 hours, it fell down by 64.3%. Within the same period, in both groups IL-6 turned out to be significantly higher than the upper reference limit. By the end of the first 24 hours, IL-6 tend to decrease in both groups; however, in the comparison group, this parameter was 15% higher than in the main group. Serum IL-10 was within the reference range in both groups. One hour after surgery, concentrationof IL-10 was exponentially growing in both groups and exceeded multifold the upper reference limit, whereas the content of IL-10 in the main group remained reliably higher: the difference amounted to 35.6% percent.Conclusion. During the postoperative period, patients undergone lung resection displayed significant changes in cytokines concentrations demonstrating an inflammation reaction. Inflammation was significant in patients who received epidural analgesia as evidenced by an altered content of anti-inflammatory cytokines.